2021
DOI: 10.21273/horttech04870-21
|View full text |Cite
|
Sign up to set email alerts
|

Oat Cover Crop and No-tillage Can Provide Weed Suppression and Alter Weed Community Dynamics in Sweet Corn

Abstract: Along with the many known benefits of cover crops, they may be an effective ecological weed management strategy in low-input agriculture. This research aimed to determine the effect of cover crops, combined with reduced-tillage and nitrogen inputs on sweet corn (Zea mays) yield and weed communities. During the 2-year study, the impact of the cover crop on yield varied. Yield within the no-till conventional treatment plots was not significantly different from the conventional treatment [6844 and 7721 lb/acre (P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
1
1

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 45 publications
0
1
0
Order By: Relevance
“…The combination of positive and negative interactions makes the predicted effect of cover crops on weed populations complicated. Several studies have demonstrated that cover crops alone may not be sufficient to reduce weed densities and need to be supplemented with other weed management tools [ 30 , 106 ].…”
Section: Success and Failure Of Cover Crops In Suppressing Weedsmentioning
confidence: 99%
“…The combination of positive and negative interactions makes the predicted effect of cover crops on weed populations complicated. Several studies have demonstrated that cover crops alone may not be sufficient to reduce weed densities and need to be supplemented with other weed management tools [ 30 , 106 ].…”
Section: Success and Failure Of Cover Crops In Suppressing Weedsmentioning
confidence: 99%